An Investment Framework for Nutrition in Afghanistan : Estimating the Costs, Impacts, and Cost-Effectiveness of Expanding High-Impact Nutrition Interventions to Reduce Stunting in the Early Years - Walters, Dylan (World Bank, Washington, DC, 2018)
This paper examines the costs, impacts, and cost-effectiveness of scaling up over five years the nutrition interventions included in Afghanistan’s Basic Package of Health Services (BPHS) as a first step in investing in the early years to build human capital. The total public investment required for the scale up to government-set program coverage levels is estimated to be 44 million US dollars per year over five years, or 1.49 US dollars per capita per year. Each dollar invested would yield at least 13 US dollars in economic returns and even under conservative assumptions regarding future economic growth, the economic benefits exceed the cost by six times which is 815 million US dollars over the productive lives of the beneficiaries. This scale up would prevent almost 25,000 child deaths and over 4,000 cases of stunting and avert a loss of 640,000 disability-adjusted life years (DALYs) and almost 90,000 cases years of anemia. Almost 100,000 more children would be exclusively breastfed. However, this scale-up would only have a marginal effect, a decrease of less than one-half percentage point on stunting prevalence because the current government-set target program coverage rates are very low for the preventive interventions that affect stunting. A substantially greater impact could be achieved if preventive interventions could be scaled to full program coverage levels, which would require less than 5 million US dollars more a year. This would triple the number of DALYs averted, double the number of deaths averted and avert almost eight times as many cases of stunting, resulting in a 2.6 percentage point decline in stunting over the five year period (from 41 percent to 38 percent). The prevalence of anemia in pregnant women could be reduced by 12 percentage points and the prevalence of exclusive breastfeeding could be increased by 18 percentage points. In addition, this investment is projected to generate economic benefits of 815 million US dollars over the productive lives of the beneficiaries. Each dollar invested would yield more than 13 US dollars in economic returns. Sensitivity analysis was conducted for the total cost, cost-effectiveness, and economic returns on investing in the BPHS nutrition interventions.